Quels impacts d’un intermédiaire dans le circuit de la tortilla de la ville de Mexico ? - Héloïse Leloup (EchoGéo)
The role of intermediary actors in food chains is still largely unknown, even though there is an increasing number of food initiatives aimed at eliminating or transforming them. This article, using the example of an intermediary-processor (a native corn tortilla producer in Mexico), contributes to exploring the new role that this pivotal actor can play in many food circuits. We used a participative methodology for assessing the impacts of urban food initiatives to explore the transformative capacities of these actors' traditional systems. The results highlight real potential impacts, particularly around the revaluation of old processing methods, nixtamalisation. However, these assets are compounded by difficulties in integrating the productive sector on the long term.